The Effect of Lo Cooler Temperature on Exhaust Gas from the Main Engine of the Logindo Overcomer - Moh. Ramandha Ari Pratama; Moejiono; Dyah Ratnaningsih; Shofa Dai Robbi; Agus Prawoto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Indonesian maritime sector is highly dependent on main engine performance, where lubricant oil (LO) cooler temperature affects exhaust gas stability. This study analyzes the causal relationship between LO cooler temperature (X) and main engine exhaust gas (Y) on MV Logindo Overcomer. Using a quantitative causal-comparative approach, data were collected from 10 purposively selected engine room crew members during 12 months of Sailing Practice through Likert scale questionnaires, observations, and engine logbooks. SPSS v.27 analysis showed descriptive statistics (X: mean=52.50; Y: mean=37.70), highly valid/reliable instruments (Cronbach's α >0.90), regression equation Y=8.423+0.558X, coefficient of determination 71.6%, and Spearman correlation r=0.894 (p=0.000). The results prove a very strong influence of LO cooler temperature on exhaust gas stability. The conclusion recommends regular cleaning of the LO cooler, replacement of accurate thermometers, real-time monitoring, and crew training to prevent combustion inefficiency and overheating, similar to the case of KM Pratiwi Raya